Oriented Growth of Neural Stem Cell–Derived Neurons Regulated by Magnetic Nanochains - Xia, Lin; Zhang, Chen; Su, Kaiming; Fan, Jiangang; Niu, Yuguang; Yu, Yafeng; Chai, Renjie (Frontiers in Bioengineering and Biotechnology, 2022)
Neural stem cell therapy has become a promising cure in treatment of neurodegenera-tive disorders. Due to the anisotropy of the nervous system, the newly derived neurons need not just the functional integrity, but also the orientedly grow to contact with the partner cells to establish functional connections. So, the oriented growth of the newly derived neurons is an key factor in neural stem cell based nerve regeneration. In nowadays, various of biomaterials have been applied to assist in the oriented growth of neural stem cells derived neurons. However, among these biomaterials, the magnetic materials applied in guiding the neuronal growth is still fewer in comparision with the other materials, such as the fibers. So in this work, we developed a magnetic assembled nanochains to guide the oriented growth of neural stem cells derived neurons. With the guidance of the magnetic nanochains, the seeded neural stem cells exhibited well arrangement , and the neural stem cells derived neurons showed well oriented growth with the orientation of the nanochains. We anticipated that the magnetic nanochains would have huge potential in stem cell based nerve regeneration.